Dork diaries : tales from a not-so-fabulous life - Russell, Rachel Renee. (Aladdin, 2009)
Fourteen-year-old Nikki Maxwell writes in her diary of her struggle to be popular at her exclusive new private school, then of finding her place after she gives up on being part of the elite group.